Generation of Maximally Entangled States by a Kerr-like Nonlinear Coupler Interacting with External Fields - Khoa, Doan Quoc; Oanh, Luong Thi Tu; Lanh, Chu Van; Dung, Nguyen Thi; Son, Do Hong (Communications in Physics, 2019)
We study a model with two nonlinear oscillators (Kerr-like nonlinear coupler) pumped by two external coherent fields as a nonlinear quantum scissor (NQS). Using the numerical simulation method introduced before for quantum state engineering in NQS of such type, we obtain the wave function describing the evolution of the system as a combination of n-photon states. Considered NQS generates a truncation of optical states that leads to achieve two-qubit states due to the nonlinear properties of oscillators and their interaction. In particular, evolution of the system generates maximally entangled states as so-called Bell-like states. We will show that a proper choice of initial conditions for such evolution implies the increase of efficiency of entanglement creation process. We consider our model for both damping and without damping cases